The eyes of the forest - Henry, April (Square Fish : Henry Holt and Company, 2022)
When popular epic fantasy writer R.M. Haldon disappears, only his teenage assistant Bridget Shepherd is concerned, compelling her to investigate what happened to him. Meanwhile, a deranged fan, Derrick, hopes to compel the author to finish the final book in his series.